2019
DOI: 10.1101/811646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dual stochasticity in the cortex as a biologically plausible learning with the most efficient coding

Abstract: Neurons and synapses in the cerebral cortex behave stochastically even during precise perception and reliable learning of animals. While studies have revealed advantages of these stochastic features, relationship and synergy of them remain elusive. Here, we show that these stochastic features are unified into a framework to provide an efficient and biologically-plausible learning algorithm that consistently explains various experimental findings of the brain, which includes statistics of cortical circuit and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Another interesting perspective was introduced by integrating stochasticity at the synaptic and neuronal levels to draw samples from the encoded distribution [75]. Here, it was shown that the fluctuations of both neural activity and synaptic weights work as the Gibbs sampling [76], generalizing learning in Boltzmann machines [77] with additional weight sampling.…”
Section: Statistical Inference Via Synaptic Stochasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting perspective was introduced by integrating stochasticity at the synaptic and neuronal levels to draw samples from the encoded distribution [75]. Here, it was shown that the fluctuations of both neural activity and synaptic weights work as the Gibbs sampling [76], generalizing learning in Boltzmann machines [77] with additional weight sampling.…”
Section: Statistical Inference Via Synaptic Stochasticitymentioning
confidence: 99%
“…Another recent work by Teramae [71] integrated two different timescales of sampling in synapse and neuron. It generalized Boltzmann machine [72] learning with additional weight sampling, and proposed that fluctuations of both neural activity and synaptic weights arose as a result of the Gibbs sampling [73].…”
Section: Intrinsic Dynamics Could Contribute To Brain Functionmentioning
confidence: 99%